2010
DOI: 10.1103/physrevlett.104.173002
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Double Ionization of Ar and Ne Close to Threshold

Abstract: In kinematically complete studies we explore double ionization (DI) of Ne and Ar in the threshold regime (I>3x10{13} W/cm{2}) for 800 nm, 45 fs pulses. The basic differences are found in the two-electron momentum distributions-"correlation" (CO) for Ne and "anticorrelation" (ACO) for Ar-that can be partially explained theoretically within a 3D classical model including tunneling. Transverse electron momentum spectra provide insight into "Coulomb focusing" and point to correlated nonclassical dynamics. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
50
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 27 publications
(30 reference statements)
7
50
1
Order By: Relevance
“…Two recent experiments have shown that at the low laser intensity, the two-electron momentum along the laser polarization exhibits a surprising anticorrelated behavior [47,48], which is completely different from that at the high laser intensity. With the semiclassical model including tunneling of the first electron and the second excited electron produced by recollision, this experimental result is well reproduced [48]. With a strong field approximation calculation, it has been demonstrated that the recollision induced excitation with subsequent tunneling ionization can result in the correlated electron momentum distribution spreading in all of the quadrants [49].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Two recent experiments have shown that at the low laser intensity, the two-electron momentum along the laser polarization exhibits a surprising anticorrelated behavior [47,48], which is completely different from that at the high laser intensity. With the semiclassical model including tunneling of the first electron and the second excited electron produced by recollision, this experimental result is well reproduced [48]. With a strong field approximation calculation, it has been demonstrated that the recollision induced excitation with subsequent tunneling ionization can result in the correlated electron momentum distribution spreading in all of the quadrants [49].…”
Section: Introductionmentioning
confidence: 92%
“…The mechanism for the electron achieving final energy above 2U p in NSDI has been well demonstrated [44][45][46]. Two recent experiments have shown that at the low laser intensity, the two-electron momentum along the laser polarization exhibits a surprising anticorrelated behavior [47,48], which is completely different from that at the high laser intensity. With the semiclassical model including tunneling of the first electron and the second excited electron produced by recollision, this experimental result is well reproduced [48].…”
Section: Introductionmentioning
confidence: 98%
“…The joint momentum distributions were also shown to be sensitive to the carrier envelope phase (CEP) of a few-cycle laser pulse [6,7]. More recent experiments on double ionization of atoms using femtosecond laser pulses continue to reveal interesting phenomena, such as the anticorrelation of the two-electron momenta [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recording the momentum spectra of doubly 10,11 and multiply 7 charged ions provided clear evidence that the emission of the second electron is triggered by the laser-driven recollision of the first electron with its parent ion. Even more insight into the process was gained in kinematically complete studies where the correlated two-electron momentum distributions were measured 11 and investigated for different laser parameters [12][13][14][15] . Measurements of the dynamics of NSDI in near-single cycle laser pulses have been restricted to recoil-ion spectra, which did not allow for the direct retrieval of the correlated electron-emission dynamics 16,17 .…”
mentioning
confidence: 99%